The effect of plyometric training and moderating variables on stretch-shortening cycle function and physical qualities in female post peak height velocity volleyball players - Sylvester, Richard; Lehnert, Michal; Hanzlíková, Ivana; Krejčí, Jakub (Frontiers in Physiology, 2024)
Purpose: Although several studies investigated the effect of plyometric training on physical performance, there is a lack of clarity regarding the effectiveness of plyometric training or its moderator variables in youth female volleyball players. The primary aim of this study was to explore the effect of horizontal plyometric training on explosive stretch-shortening cycle hops and jumps in the vertical and horizontal directions in female post peak height velocity (PHV) volleyball players. The secondary aim was to assess the influence of participant and training related moderators on horizontal plyometric training in post-PHV volleyball players. Methods: A total of 23 post-PHV volleyball players participated in this eight-week intervention with horizontal plyometric exercises, twice a week. Pre-testing and post-testing included bilateral and unilateral vertical sub-maximal hopping, horizontal jumping and hopping, and a drop jump test. The effectiveness of the intervention was assessed using a paired t-test. The influence of internal moderators such as age, maturity and body mass and external moderators such as training volume were assessed using regression and correlation analysis. Results: An eight-week plyometric training improved sub-maximal hopping at 2.5 Hz left by 4.4%, bilateral sub-maximal hopping at 2.0 Hz by 9.5% and bilateral sub-maximal hopping at 2.2 Hz by 6.8% in post-PHV female volleyball players. Horizontal jumping and hopping, reactive strength index and other sub-maximal hopping conditions did not improve significantly. Body mass had a large moderating effect on vertical unilateral sub-maximal hopping at 2.5 Hz right (p = 0.010, η2 = 0.314), vertical unilateral hopping at 3.0 Hz right (p = 0.035, η2 = 0.170), and vertical unilateral hopping at 3.0 Hz left (p = 0.043, η2 = 0.203). Training volume together with generalized joint hypermobility moderated right leg triple broad hop performance, whereas maturity and age did not moderate any variables. Conclusion: This study determined that eight weeks of horizontal plyometric training can improve unilateral absolute leg stiffness in post-PHV female volleyball players, and this training effect can be moderated by body mass. Furthermore, the training effect on triple hopping performance on the right leg can be moderated by combined training volume with generalized joint hypermobility.